Elevated Levels of Inflammatory Cytokines Predict Survival in Idiopathic and Familial Pulmonary Arterial Hypertension - Soon, Elaine; Holmes, Alan M.; Treacy, Carmen M.; Doughty, Natalie J.; Southgate, Laura; Machado, Rajiv D.; Trembath, Richard C.; Jennings, Simon; Barker, Lucy; Nicklin, Paul; Walker, Christoph; Budd, David C.; et al. (Circulation (New York, N.Y.), 2010)
Background— Inflammation is a feature of pulmonary arterial hypertension (PAH), and increased circulating levels of cytokines are reported in patients with PAH. However, to date, no information exists on the significance of elevated cytokines or their potential as biomarkers. We sought to determine the levels of a range of cytokines in PAH and to examine their impact on survival and relationship to hemodynamic indexes. Methods and Results— We measured levels of serum cytokines (tumor necrosis factor-α, interferon-γ and interleukin-1β, -2, -4, -5, -6, -8, -10, -12p70, and -13) using ELISAs in idiopathic and heritable PAH patients (n=60). Concurrent clinical data included hemodynamics, 6-minute walk distance, and survival time from sampling to death or transplantation. Healthy volunteers served as control subjects (n=21). PAH patients had significantly higher levels of interleukin-1β, -2, -4, -6, -8, -10, and -12p70 and tumor necrosis factor-α compared with healthy control subjects. Kaplan-Meier analysis showed that levels of interleukin-6, 8, 10, and 12p70 predicted survival in patients. For example, 5-year survival with interleukin-6 levels of >9 pg/mL was 30% compared with 63% for patients with levels ≤9 pg/mL ( P =0.008). In this PAH cohort, cytokine levels were superior to traditional markers of prognosis such as 6-minute walk distance and hemodynamics. Conclusions— This study illustrates dysregulation of a broad range of inflammatory mediators in idiopathic and familial PAH and demonstrates that cytokine levels have a previously unrecognized impact on patient survival. They may prove to be useful biomarkers and provide insight into the contribution of inflammation in PAH.